Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1186/s12903-023-02808-3
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic approaches and materials in restorative and regenerative dentistry: review article

Abstract: Biomimetics is a branch of science that explores the technical beauty of nature. The concept of biomimetics has been brilliantly applied in famous applications such as the design of the Eiffel Tower that has been inspired from the trabecular structure of bone. In dentistry, the purpose of using biomimetic concepts and protocols is to conserve tooth structure and vitality, increase the longevity of restorative dental treatments, and eliminate future retreatment cycles. Biomimetic dental materials are inherently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…Dental composites containing bioinspired mineral and organic components such as nanocrystalline hydroxyapatite, amino acids, polymers, etc. are the subject of current topical research. These smart materials are in demand to restore lost dental hard tissue as part of the biomimetic approach in dentistry, where it becomes possible to restore the function and vitality of teeth through restorations. This requires imitating the natural tissue: the fibrous structure and morphology of the dental organomineral complex with its unique biomechanical properties. ,, …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dental composites containing bioinspired mineral and organic components such as nanocrystalline hydroxyapatite, amino acids, polymers, etc. are the subject of current topical research. These smart materials are in demand to restore lost dental hard tissue as part of the biomimetic approach in dentistry, where it becomes possible to restore the function and vitality of teeth through restorations. This requires imitating the natural tissue: the fibrous structure and morphology of the dental organomineral complex with its unique biomechanical properties. ,, …”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the introduction of organic polymers into the composition of bioinspired material allows us to achieve chemical modification and functionalization of the formed biomimetic layer, as well as to bind it to the natural mineralized tissue. , Recently, a nature-like adhesive, polydopamine (PDA), which contains a variety of functional molecular groups, including amine, catechol, and quinone groups, has shown high potential for clinical application. ,, Due to this, PDA is able to form strong bonds with the surface of almost all known materials regardless of their chemical composition. In particular, it is known that PDA is able to bind to Ca 2+ ions of hydroxyapatite through functional groups, which contributes to the formation of a biomimetic mineralized layer. , Recently, it has been suggested that codeposition of phosphates with polydopamine (PDA) may be a simple and promising strategy to activate enamel and dentin mineralization and modify their surface . The hybrid organomineral interfaces thus formed may facilitate the regeneration of enamel-like layers in dental defect repair procedures.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In traditional dentistry, dental components are extracted and replaced with rigid materials. These methods and materials reduce restorative durability and the tooth's structural tensile strength (3).…”
Section: Introductionmentioning
confidence: 99%